Assessment of the Farmers’ Knowledge on Pesticide Usage and Classification of the Types of Pesticides Used in the Farms along Thiba River Catchment Area, Mwea Irrigation Scheme, Kirinyaga County, Kenya - Victor K. Korir; Deborah A. Abong'o; Joyce G.N. Kithure; Vincent O. Madadi (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The aim of the study was to assess the farmers’ knowledge on the safe use of pesticides, to identify the types and classify pesticides used to control pests and diseases in the catchment area using structured questionnaire, face to face interview, and focus group discussion. This was done in February and May, 2021 representing the dry and wet seasons respectively. The farmers applied 12 different pesticides, under different trade names and active ingredient. World Health Organization class Type II of the pesticides were used by 50 %, class III and IV by 25% of the farmers respectively. The WHO, Type II pesticides are considered to be toxic when manufacturers’ specifications are not adhered to and Type III are slightly toxic while IV are not toxic. Chlorpyrifos was the highest used pesticide by 72 % of the farmers followed by Lambda-cyhalothrin at 60 % while the least was Copper hydroxide by 40 %.